2017
DOI: 10.1124/jpet.117.243808
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Diacylglycerol Lipase Alpha Inhibition in the Mouse Lipopolysaccharide Inflammatory Pain Model

Abstract: Diacylglycerol lipase (DAGL) and, the major biosynthetic enzymes of the endogenous cannabinoid (endocannabinoid) 2-arachidonylglycerol (2-AG), are highly expressed in the nervous system and immune system, respectively. Genetic deletion or pharmacological inhibition of DAGL- protects against lipopolysaccharide (LPS)-induced inflammatory responses in mouse peritoneal macrophages and reverses LPS-induced allodynia in mice. To gain insight into the contribution of DAGL- in LPS-induced allodynia, we tested global k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
18
3
Order By: Relevance
“…Indeed, there are already groups working on developing DAGL inhibitors for metabolic disorders, after it was noted that DAGL KO animals are leaner and consume less food than WT littermates ( Janssen and van der Stelt, 2016 ). DAGL inhibitors are also being investigated for inflammatory pain ( Wilkerson et al, 2017 ), which could replicate some of the analgesic effects of CP without the abuse liability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are already groups working on developing DAGL inhibitors for metabolic disorders, after it was noted that DAGL KO animals are leaner and consume less food than WT littermates ( Janssen and van der Stelt, 2016 ). DAGL inhibitors are also being investigated for inflammatory pain ( Wilkerson et al, 2017 ), which could replicate some of the analgesic effects of CP without the abuse liability.…”
Section: Discussionmentioning
confidence: 99%
“…Inducing inflammatory response of macrophages to produce abnormal inflammatory pain [3133] and inducing anti-inflammatory cytokines to produce analgesia [18] might be a useful target for the development of novel therapeutics [34]. In this experiment, it was found that the infiltration and distribution of macrophages in the muscle around incisions were increased (Figure 2(d)), but there was no significant change in vascular endothelial permeability (Figure 2(a)) and the expression of p120 and Epac1 (Figure 3) in the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we should not discard that the increase in these non-NEAs mediators could contribute to our NAPE-PLD KD mice's (specifically in the vmPFC) behavioral outcomes. Similarly, DAGLα KO's effects have been investigated and shown to induce a region-dependent reduction in 2-AG, arachidonic acid, and derivatives and, in some regions, AEA (Schuele et al, 2020;Tanimura et al, 2010;Wilkerson et al, 2017). The CRISPR-Cas9 approach used in our study has the advantage of providing high selectivity towards our target (NAPE-PLD or DAGL) in a brain specific region different from global KO strategies (which are complicated by neurodevelopment adaptations) or the conditioned KO models (with considerable time investments and costs of housing in animal facilities).…”
Section: Involvement Of Nape-pld Activity In the Mpfc In The Effects Of Escitalopram Combined With Cbdmentioning
confidence: 99%
“…Therefore, we should not discard that the increase in these non-NEAs mediators could contribute to our NAPE-PLD KD mice's (specifically in the vmPFC) behavioral outcomes. Similarly, DAGLα KO's effects have been investigated and shown to induce a region-dependent reduction in 2-AG, arachidonic acid, and derivatives and, in some regions, AEA (Schuele et al, 2020;Tanimura et al, 2010;Wilkerson et al, 2017). The (which was not certified by peer review) is the author/funder.…”
Section: Involvement Of Nape-pld Activity In the Mpfc In The Effects Of Escitalopram Combined With Cbdmentioning
confidence: 99%